Retrofitting RC beams using high-early strength alkali-activated concrete. (December 2022) - Karmegam, Aarthi; Avudaiappan, Siva; Amran, Mugahed; Guindos, Pablo; Vatin, Nikolai Ivanovich; Fediuk, Roman
Abstract: Demolition of existing deteriorated structures and construction of the new structures is a costly, time-consuming, and resource-intensive process. Repair of concrete beams and strengthening techniques for existing reinforced concrete elements is a resource-saving exercise that is time-saving also. In this work, a repair material using metakaolin-based alkali-activated concrete (AAC) is developed with high early compressive strength and split tensile strength designed with proper mix proportions. The flexural strength of reinforced concrete beams was determined without the new repair material. The specimens were loaded until failure and the deflected portion of the RC beam was then confiscated using breakers. The confiscated portion is subsequently replenished with metakaolin-based AAC and flexural strength and bond characteristics were determined. Shrinkage length changes were also measured. The metakaolin-based AAC with 15% metakaolin had a high stiffness and increased flexural strength up to 14.4% compared to the specimen before repair. It also exhibited a significant bonding with the concrete substrate with less shrinkage and improved strength.